Menertawakan Absurditas Agar Tetap Waras: Humor, Nihilisme, dan Penertawa - Anodya Ariawan Soesilo (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2019)
Abstract Laughter is cloaking that has always assumed depth and shallowness. The construction of this article departs from the reading of Nietzsche’s aphoristic description in Guy Science concerning our question marks and the issue of intelligibility. The activity of laughing has personal dimension pointing to inner independence first; to a person who laugh. As long as words are part of the persona (phrosophon: ‘mask’) then the expression of laughter also points to the disguise. In reading Nietzsche, cloaking is not identical with hypocrisy. Humor can be a form of creative resistance even though it contains nihil aspect because itdoes not change any situation other than the possibility of being more tolerable. Nihilism was Nietzsche’s description of his day. The ability to laugh at oneself can be a healthy critique for those who claim to be godly. At least, in the Christian sphere laughter has religious dimension, containing the promise of salvation. In the Middle Ages, there was a tradition of humor and laughter as part of the Easter celebration (Risus Paschalis). Abstrak Tawa merupakan penyelubungan yang selalu mengandaikan kedalaman dan kedangkalan. Konstruksi tulisan ini berangkat dari pembacaan terhadap uraian aforistik Nietzsche dalam Guy Science tentang tanda tanya kita dan soal inteligibilitas. Tawa berdimensi personal menunjuk ke kemandirian sebelah dalam terlebih dulu; menunjuk pada persona yang menertawa (the laughter). Sejauh kata-kata adalah bagian dari persona (phrosophon: ‘topeng’) maka ekspresi tawa ikut menunjuk pada penyamaran itu. Dalam pembacaan Nietzsche, penyelubungan tidaklah identik dengan hipokrisi. Humor dapat menjadi bentuk resistensi kreatif kendati mengandung unsur nihil (nothing) di dalamnya sebab tak mengubah keadaanapa pun selain kemungkinan lebih dapat tertanggungkan. Nihilisme merupakan gambaran Nietzsche terhadap zamannya. Kemampuan menertawakan diri sendiri dapat menjadi kritik menyehatkan bagi kalangan yang mengaku bertuhan. Dalam lingkup kristiani, setidaknya tawa berdimensi religius, mengandung janji keselamatan. Pada Abad Pertengahan, ada tradisi humor dan tawa sebagai bagian perayaan Paska (Risus Paschalis).